Academic Migration and Epistemological Value: Exploring the Experience of Migrant Academics in Portugal - Taísa Oliveira; Cosmin Nada; António Magalhães (MDPI AG, 2023)
The internationalisation of higher education (IoHE) has become a prominent topic in higher education research. While there is increasing institutional and governmental commitment to IoHE, it is important to consider the actual outcomes of these processes critically. Despite the significant issues raised by the academic migration of professors, researchers, and post-docs regarding migratory trajectories and epistemological aspects of scholarly work, this area of research remains understudied. This article adopted a qualitative approach, drawing on semi-structured interviews with migrant scholars pursuing academic careers in Portugal. Our findings suggest that a complex interplay of factors influences the pursuit of an academic career by migrants, including the influence of institutional and governmental policies regarding science and the impact of marketisation of higher education institutions that have jeopardised academic career possibilities. Moreover, science and academic-related work seem to be the main drivers in pursuing an academic career for migrant scholars rather than primarily career-focused and economic strategies. Notwithstanding, our study highlighted the challenges that migrant academics face at the epistemological level, pointing out that their experiences are embedded in neocolonial logics that are further aggravated by current unequal societal arrangements related to what constitutes valid and legitimate knowledge and the power relations therein.